INVESTIGATING GEOPOLITICAL FACTORS OF RELIGIOUS CITIES (CASE OF STUDY: MASHHAD CITY) - Dr. Ibrahim Romina , Dr. Mahtab Jafari , Maryam Kalhor (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The security and defense approaches of every nation-state in world politics are derived from its perception of the threat posed to it from peripheral and international environment. The perceptions and misunderstandings of governments are the embodiment of their security behaviors and actions in international relations. The purpose of this study is to investigate the role of perception of threat and its effect on dominant Iranian security behavior in the Middle East. Since the victory of the Islamic Revolution, many regional governments have taken an aggressive and non-peaceful approach to the government of Iran and have perceived it as a government disrupting accepted rules of the game and also their internal stability and security. The question is "How the perception of the threat has formed the security behavior and policy of the government of the Islamic republic of Iran after the victory of the Islamic revolution?" The answer to this question, applying the theory of defensive realism, argues that threat perception by the Islamic Republic of Iran has mainly shaped its security and defensive policies in an intrinsic and unilateral threat balance in the Middle East. In this paper, the research methodology is descriptive-analytical and data collection method is library-based.